The Effect Of Corporate Social Responsibility Towards Customer Loyalty: The Role Of Trust, C-C Identification, And Customer Satisfaction - Rizal E Halim; Ahmadan Maulana Hermawan (Jurnal Manajemen, 2017)
In addition to running the rules set by the government, the activity of CorporateSocial Responsibility (CSR) is also carried out by the company in increasing customerloyalty. This study aims to analyze the influence of CSR activities at the local aircraftcompany and local banking company to customer loyaltymediatedby customer trust,C-C(Consumer-Company)identification, and customer satisfaction. Selection of these twoindustries because ofgrowththat hasoccurredeveryyear. The sample was consumers whohave used the services of local aircraft in the last six months and consumers wereregistered as clients of local banks in the six months before the study began. This studyuses Structural Equation Modeling (SEM) and found that for consumers from localaircraft, the company's CSR activities significantly affect customer loyalty throughmediation of customer trust, while consumers from local bank, CSR activitiessignificantly affect the customer loyalty through mediation of c-cidentification.